Targeted s-gram matching: a novel n-gram matching technique for cross- and monolingual word form variants - Ari Pirkola; Heikki Keskustalo; Erkka Leppänen; Antti-Pekka Känsälä; Kalervo Järvelin (Information Research: An International Electronic Journal)
We present a novel n-gram based string matching technique, which we call the targeted s-gram matching technique. In the technique, n-grams are classified into categories on the basis of character contiguity in words. The categories are then utilized in matching. The technique was compared with the conventional n-gram technique using adjacent characters as n-grams. Several types of words and word pairs were studied. English, German, and Swedish query keys were matched against their Finnish spelling variants and Finnish morphological variants using a target word list of 119 000 Finnish words. In all cross-lingual tests done, the targeted s-gram matching technique outperformed the conventional n-gram matching technique. The technique was highly effective also for monolingual word form variants. The effects of query key length and the length of the longest common subsequence (LCS) of the variants on the performance of s-grams were analyzed.